Manhaj Muktarah Li Ta’lim Al-Lughah Al-Arabiyyah Li Al Malayuwiyiin Khilali Al-Kalimat Al-Malayuwiyah Dzati Aslin Araby Fi Qamus Daya - Ilham Saputra; Mulyadi; Zulkhaidir (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2020)
هدفت هذه الدراسة إلى معرفة واكتشاف الكلمات ذات أصل عربي في قاموس دايا من حرف A إلى حرف E نموذجا، ثم تصميمها إلى المنهج المقترح لغرض تسهيل معلمين لتعليم اللغة العربية للملايويين. وكذلك لمعرفتهم على أن بين اللغتين، الملايوية والعربية علاقة قوية منذ دخول الإسلام في أرض ملايو. ولإنجاز هذه الدراسة العلمية يسلك الباحث المنهج النوعي، وذلك من خلال تصميم المنهج المقترح من الكلمات الملاوية ذات أصل عربي لتعليم اللغة العربية للملاويين، بالاعتماد على كتب تعليم اللغة العربية، والاستفادة منها في تعليم اللغة العربية للملايويين. تواصل الباحث إلى هذه الدراسة في الناتجتين؛ أولهما وجود الكلمات ذات أصل عربي في قاموس دايا وعددها وصل نحو 138 كلمة من حرف A إلى حرف E، وثانيهما أنه من خلال هذه الكلمات الملايوية يمكن تسهيل عملية التعليم والتعلم، ويكون ذلك في تصميم المنهج المناسب لهم، وذلك باستخدام تلك الكلمات التي لها أصل عربي لتعليم اللغة العربية. وتضمنت هذه الدراسة المهارات الأربع، من الحوارات، والمفردات، والتدريبات، والنصوص، وكذلك الأساليب والطرق في تعليم اللغة العربية للملايويين. This study aims to know and find Malay words derived from Arabic in the DAYA dictionary from the letter A to the letter E, then design it into the proposed curriculum to facilitate the teaching of Arabic to the Malay Community. and also to their knowledge that between the two languages, Malay and Arabic, there has been a strong connection since the introduction of Islam in Malay lands. To achieve this scientific study, researchers took a qualitative approach by designing a proposed curriculum of Malay words derived from Arabic for teaching Arabic in Malay communities, by researching Arabic textbooks and using them for teaching Arabic in Malay communitiesResearchers found two results: the first is the presence of Arabic words in the Daya dictionary and the number reaches around 138 words from the letter A to the letter E, and the second is through these Malay words, the teaching and learning process can be facilitated in designing a curriculum appropriate for the Malay community, and that is by using the words of Malay Language which originated from Arabic making it easier for Malay people to learn Arabic. This study includes four skills, and in them consists of; dialogues, vocabulary, exercises, and texts, as well as methods and methods in teaching Arabic to Malay beginners.